Prescriptions for choral excellence : tone, text, dynamic leadership - Emmons, Shirlee; Chase, Constance (Oxford scholarship online, 2023)
Presenting the most up-to-date research in voice science, and leadership, and performance psychology, this text addresses the topics most relevant to choirs, and provides instruction on how to apply the concepts in day-to-day rehearsal and performance.
Keywords: Choral conducting; Choral singing : Instruction and study; Voice culture